2021
DOI: 10.4103/ijn.ijn_84_20
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular embolization in problematic hemodialysis arteriovenous fistulas: A nonsurgical technique

Abstract: Introduction: In the past, surgical techniques were considered gold standard practice for obliterating the accessory veins, reducing the flow across the high flowing arteriovenous fistulas (AVFs), or for closing the problematic hemodialysis AVFs. However, recently endovascular embolization has emerged as a safe and cost-effective alternative to these surgical techniques. In this study, technical and clinical success, and safety of endovascular embolization have been evaluated for accessory vein ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…3,9 Endovascular covered stent placement, embolization and occlusion have emerged as the most common approaches to dealing with symptomatic or otherwise unresolved AVF in the modern era instead of open surgical options. 7 Intervention is always associated with risk, which must outweigh passivity. Covered stenting of the affected artery can be an excellent option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9 Endovascular covered stent placement, embolization and occlusion have emerged as the most common approaches to dealing with symptomatic or otherwise unresolved AVF in the modern era instead of open surgical options. 7 Intervention is always associated with risk, which must outweigh passivity. Covered stenting of the affected artery can be an excellent option.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of iatrogenic AVF due to IJV catheterization have been reported. 2 , 3 , 7 Droll and Lossing 3 cited three cases of AVF that had occurred between the right CCA and right IJV in 2004. They reported that the first AVF had occurred in 1976 from IJV catheter placement that had developed a fistula between the inferior thyroid artery and the IJV.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of tissue adhesive depended on the operator’s preference according to the access technique used (endovascular and/or surgical), the site to be treated, and the type of material required to activate a haemostatic process at the site concerned. The surgical procedure for packing an arteriovenous fistula for haemodialysis was always performed in the operating theatre [ 35 , 36 ]. Having identified the site of anastomosis between the vein and the artery (radius cephalic/humeral basilic) by ultrasound, local anaesthetic was infiltrated with an incision of the skin at the level of the distal part of the left forearm.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, it is important to intervene through urgent endovascular surgery to save the affected site and avoid the complications associated with haemodialysis catheters if thrombectomy of the fistula is unsuccessful [ 78 ]. An endovascular-covered stenthas emerged as the approach to treating symptomatic instead of open surgical options [ 79 , 80 ]. Dukkipati et al described the case of a patient on haemodialysis for 6 months ineligible for the creation of a fistula due to the suboptimal size of the vein.…”
Section: Clinical Applications Of Covered Stentsmentioning
confidence: 99%